Working Towards Recovery: The Role of Employment in Recovery From Serious Mental Health Problems: A Qualitative Meta-synthesis. - Walsh , Fran P (International Journal of Psychosocial Rehabilitation, 2013)
Objective: The objective of this review was to identify and synthesise existing qualitative literature relating to the meaning of work for individuals experiencing serious mental health problems, with particular reference to their recovery. Method: A systematic literature search and appraisal identified six qualitative studies to be reviewed. These were analysed using a meta-ethnographic methodology. Results and conclusions: Four key meta-themes were identified: self-efficacy, identity, belonging and the instrumental characteristics of work. The resultant analysis suggested that each of these interact with the intra-psychic and social domains of the individual to construct a nuanced picture of the meaning and value of work to people with mental health difficulties. The findings suggest that further research is necessary to distinguish the value of work from other meaningful activity in promoting recovery. It is hoped that synthesising existing qualitative studies will in- form thinking and research regarding work and recovery from mental health problems.